P09.37 Syphilis rapid test validation for treponemal diagnosis in guatemala, 2013–2014. (13th September 2015) - Arana Flora, E; Castillo-Signor, L; Marchorro, P; Girón, V; Lopez, A; Escobar, C; Vargas, C; Mendizabal-Burastero, R; Morales-Miranda, S
Abstract : Background: International guidelines for syphilis testing recommend non-treponemal tests, and confirmation by more complex treponemal test such as Treponema pallidum haemagglutination (TPHA), enzyme-linked immunosorbent assay (ELISA) or others. Similar to HIV rapid tests, rapid treponemal tests can improve point-of-care testing in laboratories with limited capacities. We present main results of a validation for treponemal diagnosis performed in Guatemala. Methods: A syphilis rapid test laboratory validation was performed in two phases during 2013–2014. First stage was performed using frozen serums from National Health Laboratory and second stage was performed using whole blood from pregnant women from peripheral health services from Guatemala City. Four treponemal rapid tests were evaluated in the first stage: Determine TP (DetTP), SD Syphilis (SDSyp), Omega Visitect (OVis), and Rapid Syphilis (RSyp). Only two tests were evaluated in the second stage: DetTP and SDSyp. For confirmation, TPHA was used for diagnosis of treponemal antibodies in serum and treponemal ELISA for plasma. Results: A total of 460 serums were evaluated in first stage and 432 whole blood samples in second stage. Compared to TPHA, sensitivity ranged from 87.8% for RSyp to 99.2% in DetTP in serum and 100% for SDSyp and DetTP in whole blood. Specificity was lower, ranging from 74.8% for DetTP to 87.7% for SDSyp in serum and 100% for SDSyp and DetTP in whole blood. Conclusion: Rapid treponemal tests are a useful diagnostic tool in syphilis. Sensibility was high enough to be used as a screening test, with good results in whole blood samples. Low prevalence of syphilis in the validation contributed to poor positive predictive values. The use of a reverse algorithm might be useful for implementation of this test in Guatemala. Disclosure of interest statement: We declare that we have no conflicts of interest.